Characteristics and mechanism of adsorption of tartaric acid by carbide slag ascertained and applied to prepare a binder. (20th February 2022) - Qin, Yihe; Zhang, Kai; He, Xuwen
Abstract: Pelletization is essential for the reutilization of mineral fines, and binder plays a crucial role in preparing pellets that satisfy strength requirements. In this study, carbide slag (CS) was modified with tartaric acid (TA) using a novel binder (TACS) to produce red mud pellets. In this study, to investigate the effect of TACS on the compressive strength of the pellets and ascertain the mechanism of adsorption of TA onto CS during pelletizing and adsorption experiments, the changes in crystal structure, functional groups, and valence states of elements in a solution of CS in TA were analyzed, and density functional theory calculations and molecular dynamics simulations were performed. The target pellet strength was achieved by using TACS to prepare cold-pressed red mud pellets at a solid-to-liquid ratio of 0.20. The pH of the TA solution used to prepare the binder was 13.00. The maximum adsorption capacity of CS for TA, calculated using the Langmuir model, was 336.33 mg·g −1 . The TACS was analyzed using X-ray powder diffraction, Fourier-transform infrared spectroscopy, Brunauer-Emmett-Teller method, and X-ray photoelectron spectroscopy. The analysis results confirmed that the TACS mainly comprised Ca(OH)2 and that the adsorption of TA onto CS involved complexation and hydrogen bonding. The complexing reactions of the carboxyl and hydroxyl groups of TA with the Ca ion were dominant. This study provides experimental and theoretical guidance for future studies on the preparation of composite binders.